1995
DOI: 10.1136/gut.36.5.737
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and cytokine induced expression of HLA molecules, secretory component, and intercellular adhesion molecule-1 is modulated by butyrate in the colonic epithelial cell line HT-29.

Abstract: (Gut 1995; 36: 737-742)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 20 publications
4
36
0
Order By: Relevance
“…Such cytokine-mediated up-regulation of pIgR is known to depend on de novo protein synthesis (8 -11), and has recently been shown to take place at the level of transcription in which IL-4 had the greatest effect on the transcription rate of the tested cytokines (10). This effect of IL-4 has been observed both in a human lung carcinoma cell line, Calu-3 (11,12), and in a human colonic carcinoma cell line, HT-29 (13,14). Furthermore, IL-4-mediated up-regulation of pIgR is known to be sensitive to inhibitors of tyrosine phosphorylation, indicating a signaling pathway dependent on protein tyrosine phosphorylation (11,15).…”
mentioning
confidence: 96%
“…Such cytokine-mediated up-regulation of pIgR is known to depend on de novo protein synthesis (8 -11), and has recently been shown to take place at the level of transcription in which IL-4 had the greatest effect on the transcription rate of the tested cytokines (10). This effect of IL-4 has been observed both in a human lung carcinoma cell line, Calu-3 (11,12), and in a human colonic carcinoma cell line, HT-29 (13,14). Furthermore, IL-4-mediated up-regulation of pIgR is known to be sensitive to inhibitors of tyrosine phosphorylation, indicating a signaling pathway dependent on protein tyrosine phosphorylation (11,15).…”
mentioning
confidence: 96%
“…Evidence suggests that SCFAs, particularly butyrate, serve as the principal metabolic fuel for colonic epithelial cells and exert a variety of effects fundamental to the health of normal colonic mucosa (47). For example, butyrate plays an essential role in suppressing mucosal inflammation (26,34) and exhibits antitumorigenic effects such as induction of cell cycle arrest, differentiation, and apoptosis (20,23,40,57). Butyrate is also known to stimulate colonic electroneutral NaCl absorption and to inhibit Cl Ϫ secretion (2,45).…”
mentioning
confidence: 99%
“…It has recently been reported that infection with reovirus up-regulates expression of pIgR in the human intestinal epithelial cell-line HT29 (18). Butyrate, a bacterial fermentation product and important energy source in the colon, has also been shown to up-regulate pIgR expression in HT29 cells (19). A role for commensal bacteria in pIgR regulation was suggested by the observation that intestinal pIgR mRNA levels were up-regulated when germfree mice were colonized with Bacteroides thetaiotaomicron, a prominent bacterium of the intestinal flora (20).…”
mentioning
confidence: 99%